INTRODUCTION OF BREAK EVEN POINT (BEP) ANALYSIS AS STOCK FOR STUDENTS OF FOOD SCIENCE AND TECHNOLOGY IN GROWING THE ENTREPRENEURIAL SOUL - Utami, Suci Nur; Adita, M. Dini (STKIP Santu Paulus Ruteng, 2019)
Break Even Point Analysis (BEP) is one of the tools in economic analysis that can be used to assess the feasibility of a business. The business is feasible if the income value is greater than the BEP value. The vision of the Food Science and Technologies Program is